Patterns and Processes in Marine Microeukaryotic Community Biogeography from Xiamen Coastal Waters and Intertidal Sediments, Southeast China - Chen, Weidong; Pan, Yongbo; Yu, Lingyu; Yang, Jun; Zhang, Wenjing (Frontiers in Microbiology, 2017)
Microeukaryoties play key roles in the structure and functioning of marine ecosystems. Little is known about the relative importance of the processes that drive planktonic and benthic microeukaryotic biogeography in subtropical offshore areas. This study compares the microeukaryotic community compositions (MCCs) from offshore waters (n = 12) and intertidal sediments (n = 12) around Xiamen Island, southern China, using high-throughput sequencing of 18S rDNA. This work further quantifies the relative contributions of spatial and environmental variables on the distribution of marine MCCs (including total, dominant, rare and conditionally rare taxa). Our results showed that planktonic and benthic MCCs were significantly different, and the benthic richness (6627 OTUs) was much higher than that for plankton (4044 OTUs) with the same sequencing effort. Further, we found that benthic MCCs exhibited a significant distance-decay relationship, whereas the planktonic communities did not. After removing two unique sites (N2 and N3), however, 72% variation in planktonic community was explained well by stochastic processes. More importantly, both the environmental and spatial factors played significant roles in influencing the biogeography of total and dominant planktonic and benthic microeukaryotic communities, although their relative effects on these community variations were different. However, a high proportion of unexplained variation in the rare taxa (78.1% to 97.4%) and conditionally rare taxa (49.0% to 81.0%) indicated that more complex mechanisms may influence the assembly of the rare subcommunity. These results demonstrate that patterns and processes in marine microeukaryotic community assembly differ among the different habitats (coastal water vs. intertidal sediment) and different subcommunities (total, dominant, rare and conditionally rare microeukaryotes), and provide novel insight on the microeukaryotic biogeography and ecological mechanisms in coastal waters and intertidal sediments at local scale.